Ozone nanobubble modulates the innate defense system of Nile tilapia (Oreochromis niloticus) against Streptococcus agalactiae - Nguyen Vu Linh (2022)
Ozone nanobubble (NB–O3) is a promising technology for improving dissolved oxygen and reducing bacterial concentration in aquaculture systems. Here, we investigated the effects of NB-O3 on the innate immunity of fish by monitoring the expression levels of nonspecific immune-related genes (IL-1β, IL-2β, TNF-α), heat-shock protein genes (HSP70, HSP90-α), and a bacteriolytic enzyme, C-type lysozyme, gene (LYZ) post-treatment with this technology. Following exposure to NB-O3, the different tissues of Nile tilapia (Oreochromis niloticus) were collected over time for quantitative real-time PCR (qPCR) analysis. The expression of all the genes evaluated in the gills, the head kidney, and the spleen of the NB-O3 treated group was significantly up-regulated compared to that in the untreated control group. The expression levels were the highest (approx. 2 to 4-fold) at 15 min and 3 h post-exposure and then decreased from 6 to 24 h. These findings suggested that NB-O3 could switch on the innate immunity genes of Nile tilapia. Thus, we hypothesized that the NB-O3-immune-activated fish would respond more effectively to subsequent bacterial infections, thereby improving survivability compared to that of untreated fish. To test this hypothesis, 3 h post NB-O3 exposed fish and unexposed fish were challenged with a lethal dose of Streptococcus agalactiae. Interestingly, the survival rate of the NB-O3 group was significantly higher than that of the non-treated controls, with a relative percent survival (RPS) of 60–70%. Together, these findings indicate, for the first time, that NB-O3 may trigger the nonspecific defense system of the fish, thereby improving fish survivability during subsequent bacterial infections. This research identified another potential benefit of NB-O3 in aquaculture for preventing infectious bacterial diseases.